2013
DOI: 10.1039/c3ob27273g
|View full text |Cite
|
Sign up to set email alerts
|

‘Click’ functionalised polymer resins: a new approach to the synthesis of surface attached bipyridinium and naphthalene diimide [2]rotaxanes

Abstract: Herein we describe the design and synthesis of a series of solid-tethered [2]rotaxanes utilising crown ether-naphthalene diimide or crown ether-bipyridinium host guest interactions. TentaGel polystyrene resins were initially modified in a two-stage procedure to azide functionalised beads before the target supramolecular architectures were attached using a copper catalysed "click" procedure. The final assembly was examined using IR spectroscopy and gel-phase (1)H High Resolution Magic Angle Spinning (HR MAS) NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…This red coloration is indicative of a charge-transfer phenomenon between the p-rich dialkoxynaphthalene motifs of the macrocycle and the p-deficient naphthalene diimide motif in the thread, and has been seen in related solution and surface-bound rotaxanes. [28,30,31] This qualitatively suggests at least some rotaxane assembly at the beadsolvent interface. 1 H HR-MAS NMR analysis indicated that rotaxane formation had occurred on the surface as evidenced by the diimide peak at 8.03 ppm; however, peaks for the macrocycle napthoquinone protons were obscured under the bead and stopper aromatic protons (see Figure 7).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…This red coloration is indicative of a charge-transfer phenomenon between the p-rich dialkoxynaphthalene motifs of the macrocycle and the p-deficient naphthalene diimide motif in the thread, and has been seen in related solution and surface-bound rotaxanes. [28,30,31] This qualitatively suggests at least some rotaxane assembly at the beadsolvent interface. 1 H HR-MAS NMR analysis indicated that rotaxane formation had occurred on the surface as evidenced by the diimide peak at 8.03 ppm; however, peaks for the macrocycle napthoquinone protons were obscured under the bead and stopper aromatic protons (see Figure 7).…”
Section: Resultsmentioning
confidence: 88%
“…The bound diimide proton chemical shift is consistent with that seen in related surface-bound diimide-containing rotaxanes. [30,31] Nevertheless, it is clear that significant amounts of uncomplexed diimide thread remain on the surface, and future work will look at optimizing reaction conditions to favor the formation of interlocked architectures at the solution:surface interface. …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It could be shown that HR-MAS can provide significant line narrowing by using a magnetic-susceptibility-matching probe technology [17]. While first HR-MAS examples included the investigation of resins for combinatorial chemistry [18], solvent swollen polystyrene gels [19], and lipid systems [20], more recent examples used this technique for the direct monitoring of hydrolytic degradation of biodegradable cross linked polymer network [21], estimation of cross link density of poly (dimethyl siloxane) (PDMS) networks [22], analysis of the polymer resins functionalization [23], or the study of water/polymer interactions in a poly(amidoamine) hydrogel [24].…”
Section: Introductionmentioning
confidence: 99%